Answer:
![\boxed{\boxed{\sf x=\frac{23}{10}}\: \sf or \:\boxed{x=2.3}}](https://tex.z-dn.net/?f=%5Cboxed%7B%5Cboxed%7B%5Csf%20x%3D%5Cfrac%7B23%7D%7B10%7D%7D%5C%3A%20%5Csf%20or%20%5C%3A%5Cboxed%7Bx%3D2.3%7D%7D)
_________________
![\boxed{\sf Step\: By\:Step:- }](https://tex.z-dn.net/?f=%5Cboxed%7B%5Csf%20Step%5C%3A%20By%5C%3AStep%3A-%20%7D)
![\sf 3x-\left(2x-1\right)=7x-\left(3\times \:5x\right)+\left(-x+24\right)](https://tex.z-dn.net/?f=%5Csf%203x-%5Cleft%282x-1%5Cright%29%3D7x-%5Cleft%283%5Ctimes%20%5C%3A5x%5Cright%29%2B%5Cleft%28-x%2B24%5Cright%29)
<u>Remove the parentheses:</u>
![\to\sf 3x-\left(2x-1\right)=7x-3\times \:5x-x+24](https://tex.z-dn.net/?f=%5Cto%5Csf%203x-%5Cleft%282x-1%5Cright%29%3D7x-3%5Ctimes%20%5C%3A5x-x%2B24)
<u>Combine like terms:</u>
![\sf ^*7x-x=6x](https://tex.z-dn.net/?f=%5Csf%20%5E%2A7x-x%3D6x)
![\to\sf 3x-\left(2x-1\right)=6x-3\times \:5x+24](https://tex.z-dn.net/?f=%5Cto%5Csf%203x-%5Cleft%282x-1%5Cright%29%3D6x-3%5Ctimes%20%5C%3A5x%2B24)
<u>Multiply 3 and 5x = 15x:-</u>
![\to\sf 3x-\left(2x-1\right)=6x-15x+24](https://tex.z-dn.net/?f=%5Cto%5Csf%203x-%5Cleft%282x-1%5Cright%29%3D6x-15x%2B24)
<u>Combine like terms:</u>
![\sf ^*6x-15x=-9x](https://tex.z-dn.net/?f=%5Csf%20%5E%2A6x-15x%3D-9x)
![\to\sf 3x-\left(2x-1\right)=-9x+24](https://tex.z-dn.net/?f=%5Cto%5Csf%203x-%5Cleft%282x-1%5Cright%29%3D-9x%2B24)
<u>Expand: 3x-(2x-1)= x+1</u>
![\to\sf x+1=-9x+24](https://tex.z-dn.net/?f=%5Cto%5Csf%20x%2B1%3D-9x%2B24)
<u>Subtract 1 from both sides:</u>
![\to\sf x+1-1=-9x+24-1](https://tex.z-dn.net/?f=%5Cto%5Csf%20x%2B1-1%3D-9x%2B24-1)
![\to\sf x=-9x+23](https://tex.z-dn.net/?f=%5Cto%5Csf%20x%3D-9x%2B23)
<u>Add 9x to both sides:</u>
![\to\sf x+9x=-9x+23+9x](https://tex.z-dn.net/?f=%5Cto%5Csf%20x%2B9x%3D-9x%2B23%2B9x)
![\to\sf 10x=23](https://tex.z-dn.net/?f=%5Cto%5Csf%2010x%3D23)
<u>Divide both sides by 10:</u>
![\to\sf \cfrac{10x}{10}=\cfrac{23}{10}](https://tex.z-dn.net/?f=%5Cto%5Csf%20%5Ccfrac%7B10x%7D%7B10%7D%3D%5Ccfrac%7B23%7D%7B10%7D)
![\to\sf x=\cfrac{23}{10}](https://tex.z-dn.net/?f=%5Cto%5Csf%20x%3D%5Ccfrac%7B23%7D%7B10%7D)
<u>________________________________</u>
N an acute angle is 90 degrees or less and 90 + 90 is 180 and an obtuse angle is always more than 90 and always less than 180
Answer:
- See attachment for table values
- y₁ = y₂ for x = 6
Step-by-step explanation:
In each case, put the x-value in the formula and do the arithmetic. If you're allowed, you can save some time and effort by realizing that the solution (x) will have to be an even number.
y₁ is an integer value for all integer values of x. y₂ is an integer value for even values of x only. y₁ and y₂ will both be integers (and possibly equal) only when x is even.
For example, for x = 6, we have
... y₁ = 3·6 - 8 = 18 -8 = 10
... y₂ = 0.5·6 +7 = 3 +7 = 10
That is, for x = 6, both columns of the table have the same number (10). That is, y₁ = y₂ for x = 6. The solution to the equation
... y₁ = y₂
is
... x = 6.
Answer:
store 2
Step-by-step explanation:
This is because store one sells notebook for 5.13. Store 2 sells one notebook for 1.68, and the last stores sells one notebook for 2 or 1.75. Meaning that store 2 sells it for cheap.
Answer:
x = - 5
Step-by-step explanation:
Given
5x + 7 = 2x - 8 ( subtract 2x from both sides )
3x + 7 = - 8 ( subtract 7 from both sides )
3x = - 15 ( divide both sides by 3 )
x = - 5